Is Monkeypox Being Underdiagnosed in Countries with More Stigmatizing Attitudes towards Men Who Have Sex with Men? A Simple Ecological Analysis - Chris Kenyon (MDPI AG, 2022)
It is not known why the recent outbreak of monkeypox (MPX) has been more extensive in certain European countries than others. Previous studies have found that European countries with more stigmatizing attitudes to homosexuality have more undiagnosed HIV infections in men who have sex with men (MSM). We hypothesized that MPX in MSM may be underdiagnosed in European countries with more stigmatizing attitudes to homosexuality and less access to sexually transmitted infection (STI) testing for MSM. To test this hypothesis, we used Spearman's correlation to assess if the national incidence of MPX in European countries was negatively associated with the intensity of screening for STIs and a composite indicator of Lesbian Gay Bisexual Transgender Intersex (LGBTI) rights (the Rainbow Index). We found that the national cumulative incidence of MPX was positively correlated with the intensity of chlamydia/gonorrhoea screening (rho 0.68, p-value < 0.0001), syphilis screening (rho 0.62, p-value < 0.0001), and the Rainbow Index (rho 0.65, p-value < 0.0001). Our analysis thus suggests caution is required in interpreting the relatively lower incidence of MPX reported from several Eastern European countries. A key limitation of this analysis is that the incidence of MPX was calculated in the whole population and not limited to the MSM population.